Development of Learning Media for Biolarga (Biology of Snakes and Ladders) Containing Critical thinking Skills in Class IX Human Reproductive System Material - Ernawati, Wahyuni Tri; SM, Ismail; Anggis, Eka Vasia (Universitas Islam Negeri Walisongo Semarang, 2024)
This research analyzes the characteristics and feasibility of developing biolarga (biology of snakes and ladders) learning media containing critical thinking skills on human reproductive system material. Development is carried out using a 4D development model (Define, Design, Develop, Disseminate). Learning media was developed and tested on MTs N 3 Grobogan class IX students. The data collection instrument uses a validation sheet to determine product suitability through validators, media experts, language experts, material experts, critical thinking experts, and practitioner experts. Based on the results of the validation and trials on students, the average percentage of eligibility was 84.28%. The result of this research indicates that the learning media developed is suitable for use as a medium to support the learning process, especially regarding the human reproductive system